Attitudes of Tribal Dairy Farmers Towards Dairy Entrepreneurship in Balrampur District of Chhattisgarh: A Principal Component Analysis - Gupta, Ravi Kumar; Saha, Anindita; Tiwari, Pravin Kumar; Dhakre, Digvijay Singh; Gupta, Ankur (Indian Journal of Extension Education, 2020)
Dairy farming is not an essential part of farming but also the most appropriate productive system, with enormous potential for improving the socio-economic status of large proportions of farmers in tribal areas. The study was conducted during 2018-19 to assess the attitudes of tribal dairy farmers towards dairy entrepreneurship in Balrampur district of northern hill region, Chhattisgarh through the principal component analysis. The results (BTS = 253.977 and the point of significance in P=0.00) showed that the data are appropriate for the Principal component analysis. KMO’s sample adequacy calculation result was 0.594, indicating that there were enough indications in each element for study. Factor analysis for attitudes of tribal dairy farmers towards dairy entrepreneurship identifying operational factors have put up an intrinsic relational conglomeration of the items to ultimately form a homogenous 13 attitudes items, and these items were conglomerated into 4 factors as attitudes towards; feeding management, scientific management, socio – economically and scientific production respectively.
Keywords: Attitudes; Dairy entrepreneurship; Principal component analysis; Socio-economics; Tribal dairy farmers